초등 영어학습자의 Wh-의문문 습득 연구: 의문사, 조동사, 이동 규칙의 명시적 교수가 도치 습득에 미치는 영향 - 강지혜; Jihye Kang (English teaching (KATE. Online), 2025)
This study examined subject-auxiliary inversion errors in wh-questions produced by 88 Korean EFL elementary learners, focusing on whether types of wh-words and auxiliaries could affect inversion acquisition and whether explicit instruction on movement rules could facilitate this process. Guided writing tasks were used as a pretest and a posttest to analyze influence of wh-words and auxiliaries on learners’ inversion in the pretest and effects of instruction on movement rules in the posttest. Results showed that both whwords and auxiliaries significantly influenced learners’ inversion acquisition. Learners struggled more with why-questions than with what-questions, which were selected as representatives of adjunct and argument wh-questions, respectively. More inversion errors occurred in wh-questions requiring do-support than in those involving auxiliary be or modal will, although no significant difference was found between be and will. Experimental lessons with brief explicit instruction on auxiliary movement during regular classes significantly improved learners’ inversion accuracy, particularly in dosupport questions, which posed the greatest challenge in the pretest.